2010
DOI: 10.1542/peds.2010-0852
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Patient Health Questionnaire-9 Item for Detecting Major Depression Among Adolescents

Abstract: Objective The purpose of this study was to examine the performance characteristics and validity of the Patient Health Questionnaire - 9 item (PHQ-9) as a screening tool for depression among adolescents. Methods The PHQ-9 was completed by 442 youth (13-17 years) who were enrolled in a large healthcare delivery system and participating in a study on depression outcomes. Criterion validity and performance characteristics were assessed against an independent structured mental health interview (the Child Diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
475
2
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 626 publications
(521 citation statements)
references
References 19 publications
(30 reference statements)
11
475
2
8
Order By: Relevance
“…Moreover, PHQ-9 was originally developed for adults, although nowadays it is also used in adolescents. 40 This study was cross-sectional, not longitudinal; thus, if there is causality, it could be reverse, meaning that depressive symptoms may lead to BID. Finally, as our research was carried out in a private school, we cannot extrapolate conclusions to other populations (e.g., students of public schools).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, PHQ-9 was originally developed for adults, although nowadays it is also used in adolescents. 40 This study was cross-sectional, not longitudinal; thus, if there is causality, it could be reverse, meaning that depressive symptoms may lead to BID. Finally, as our research was carried out in a private school, we cannot extrapolate conclusions to other populations (e.g., students of public schools).…”
Section: Discussionmentioning
confidence: 97%
“…It has been validated for use in Nigeria by Adewuya et al [10] who reported an internal consistency of 0.85 and optimal cut-off score for depressive disorder as 5 (sensitivity 0.897, specificity 0.989, positive predictive value 0.875, negative predictive value 0.981). The PHQ-A was modified from PHQ-9 for use in adolescents where it also has acceptable psychometric properties [14] [15] [16].…”
Section: Methodsmentioning
confidence: 99%
“…A commonly used rating scale for pediatric depression is the Patient Health Questionnaire. 9 This rating scale can be administered easily in a primary care office. Once stabilized, monthly check-ins with the pediatrician are reasonable as well as symptom check Healthy Baby/Healthy Child lists periodically (every 3 months is a reasonable regimen).…”
Section: Follow Up and Dose Adjustmentmentioning
confidence: 99%